2020
DOI: 10.1049/iet-epa.2019.0372
|View full text |Cite
|
Sign up to set email alerts
|

Application of iron nitride compound as alternative permanent magnet for designing linear generators to harvest oceanic wave energy

Abstract: Most of the conventional linear generator is constructed with either Alnico (specially AlNiCo-9) or Neodymium iron boron (NdFeB) permanent magnets (PMs) for harvesting oceanic wave energy. Alnico is a composition of aluminium (Al), nickel (Ni), and cobalt (Co) added to iron, which is its major volumetric component. Alnico has a poor magnetic energy product, and NdFeB contains a rare earth element. To overcome this issue, a recently developed rare-earth free iron nitride (Fe 16 N 2) compound-based PM linear gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The simulation results show that the output-induced voltages could be increased by using high-grade NdFeB PMs. Due to the high price of the NdFeB and the environmental aspects, the alternative has been proposed to replace the NdFeB magnets [98]. The temperature rises during the operation of the linear generator, and this rising heat can demagnetise the magnets.…”
Section: Application Of High-grade Pms and Solving The Demagnetisatio...mentioning
confidence: 99%
“…The simulation results show that the output-induced voltages could be increased by using high-grade NdFeB PMs. Due to the high price of the NdFeB and the environmental aspects, the alternative has been proposed to replace the NdFeB magnets [98]. The temperature rises during the operation of the linear generator, and this rising heat can demagnetise the magnets.…”
Section: Application Of High-grade Pms and Solving The Demagnetisatio...mentioning
confidence: 99%
“…Moreover, the dehumidifier controls the humidity in the linear generator which would increase its lifespan. Other than these permanent magnets, the compound Fe 16 N 2 known as iron nitride is applied in [32] which exhibits the best performance among all conventional rare earth free permanent magnets. Table 2 presents outcomes of the LG for application of various high graded permanent magnets along with conventional one.…”
Section: ) Temperature Minimization In the Pmlgmentioning
confidence: 99%
“…It is also very important to maintain a proper supply chain to meet the demand for the development of highly advanced technologies. Even the substitution of REE by other cheaper metals is difficult for most applications, though powerful permanent magnets made out of iron and nitrogen (iron nitride, Fe16N2) are helping the automotive and wind energy industries in a small way [7]. Pavel et al [8] studied the possibilities of substitution of REE in wind turbines in order to reduce the dependency on REE, but later it was found that these claims were impossible without neodymium.…”
Section: Introductionmentioning
confidence: 99%